Studies employing the unified theory of acceptance and use of technology (UTAUT) as a guideline for the research: Literature review of the Saudi context. - Alshabeb, Abdulrahman M.; Alharbi, Omran; Almaqrn, Riam K.; Albazie, Haifa Abdullah (Advances in Social Sciences Research Journal, 2020)
Theoretical framework models are widely employed by researchers because these models are able to provide an in-depth understanding of the phenomena under investigation. The models most commonly adopted by researchers in the field of e-learning are the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). This paper presents a review of studies that have included the UTAUT framework as a guideline for the research. More specifically, this paper concentrates on research that has been conducted in Saudi Arabia. The results of this review indicate that according to the review and an analysis of previous studies, facilitating conditions, performance expectancy and effort expectancy have positive effects on users’ intentions to integrate and adopt E-Learning technologies. Finally, this paper presents and highlights area for future work.